2018
DOI: 10.4269/ajtmh.18-0100
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: First Report of Autochthonous Human Cutaneous Myiasis Caused by Hypoderma lineatum in Europe

Abstract: We report a case of human cutaneous myiasis by , contracted by a farmer who never traveled outside Italy. Identification at species level has been performed by both morphological examination and sequencing of cytochrome c oxidase subunit I gene. This is the first description of human hypodermosis by contracted in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…According to data presented by Hassan et al [ 15 ], the most common species of Hypoderma are H. bovis and H. lineatum when it comes to domestic cattle. H. bovis is frequently reported in countries from the northern hemisphere, and its pathogeny is of greater importance to farmers, considering the severity of lesions that this infection might induce if treatment is not instituted promptly (when first-stage larvae are in the peri-rachidian channel, in the absence of treatment, they might induce paralysis of the hind quarters) [ 13 ]. The results of the morphological identification doubled by PCR assays based on mitochondrial COI sequencing for the identification of H. bovis [ 28 ] performed during our study revealed the presence of H. bovis with two haplotypes: HB3 and HB8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to data presented by Hassan et al [ 15 ], the most common species of Hypoderma are H. bovis and H. lineatum when it comes to domestic cattle. H. bovis is frequently reported in countries from the northern hemisphere, and its pathogeny is of greater importance to farmers, considering the severity of lesions that this infection might induce if treatment is not instituted promptly (when first-stage larvae are in the peri-rachidian channel, in the absence of treatment, they might induce paralysis of the hind quarters) [ 13 ]. The results of the morphological identification doubled by PCR assays based on mitochondrial COI sequencing for the identification of H. bovis [ 28 ] performed during our study revealed the presence of H. bovis with two haplotypes: HB3 and HB8.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate of parasitism with H. bovis resulting from this study is fairly low compared with previously conducted studies, which reported prevalence rates between 32 and 43%, [16,17], 16.21% in Southern Romania [18]or with other countries: up to 85% in Italy [19,20], 67% in Turkey, 23% in Iraq [21], 43% in Belgium, 40% in France, 37.4% in Greece [22], 52.3% in Spain, 16% in Poland, 20% in Switzerland, up to 80% in China [23], and 31.1% in Albania [24]. The prevalence rate recorded 25 (2-7) 48 (6)(7)(8)(9)(10)(11)(12)(13)(14) 20 (1-5) 23 (5)(6)(7)(8)(9)(10) 106 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) May (Max-Min) June (Max-Min) p value equals 0.5861 By conventional criteria, this difference is considered to be not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the available information, H. bovis appears to be more dominant in central, eastern and northern Europe. Hypoderma lineatum , however, seems to be the predominant species in North America and southern Europe [9, 10] where it has been rarely reported to infest humans causing creeping subdermal myiasis [11–13] as the host specificity is not absolute.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, a case report was published, describing a farmer, who had never travelled outside Italy with an infestation by H. lineatum , confirmed by molecular analysis. 3 Puente et al. (2010) reported on a European with an H. sinense infestation, presenting with abdominal pain and, inflammation of the right groin and testicular region after traveling to northern India.…”
mentioning
confidence: 99%